IN 2020 WHAT TEACHING METHODOLOGIES ARE USED IN FOOTBALL SPORT SCHOOLS - Albano, Danilo Cunha; Azevedo, Gustavo Batista de; Santos, Juliana Rodrigues dos; Santana, Jeferson; Lopes Verardi, Carlos Eduardo [UNESP]; Franca, Elias de; Caperuto, Erico Chagas; Fukushima, Andre Rinaldi; Hirota, Vinicius Barroso (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2021)
Football is one of the best known and most practiced sports in the world, promoting direct and indirect involvement in all it players, of different ages and social classes, influencing their entire environment and indirectly everything around them.In this sense our study comes to make a survey with professionals who work with the football modality and be able to observe if the methodologies used have evolved in the practical context, and as a Qualitative Descriptive field surveywas carried out in the form of a questionnaire with fifteen coaches and teachers of football teams. The results shows that the coaches have experience in different methodologies of teaching football and the most used method to teaching football is the Global-functional, instead that the most know method is the analytical-synthetic showed by the results of the coaches so in 2020 there is a tendency to work with methodologies that involves the group of young athletesleaving theymore motivated.
Keywords: Football; Teaching methodology; Global Method; Analytical-Synthetic Method; Cildren